PERAN PESANTREN MENGHADAPI KONSTELASI ERA 4.0 - Nur Rohmah Hayati (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
Indonesia is currently entering the era of the Industrial Revolution 4.0. Mid-century (digital revolution) was marked by a combination of technology and blurring of physical, digital space lines. Changes in the world in the era of the Industrial revolution which is so fast certainly provide demands for progress. Islamic boarding schools or Islamic boarding schools are one of the Islamic education in Indonesia. The reform and reconstruction of Islamic education and its institutions seems to need to be carried out immediately, especially looking at the development of the world which requires that every Islamic education institution be it Islamic boarding schools or madrasas to continue to improve themselves if they do not want to be abandoned by their interested ones. The inclusive attitude of Islamic education in this context is very necessary. inclusiveness becomes very important given that however, Islamic education institutions cannot isolate themselves from the dynamics that occur outside themselves. Era of Industrial Revolution 4.0 (hereinafter: Era 4.0) has an unimportant impact. It affects all aspects of human life. Included in this case is education. This era was marked by the increasingly central role of cyber technology in human life. The challenges of the Industrial Revolution 4.0 era are very complex. Not to mention in the world of education, all have already converted in the digital world. If in the past it was quite a manual, old-fashioned, primitive system, now everything must be completely cyber. Examples of e-library (digital library), e-learning (digital learning), e-books (online books).